Researching the Police in the 21st Century
XV, 220 p.
Keywords: This unique collection explores the importance of undertaking police research, using a range of international examples from USA, UK and Germany. Focusing on practical challenges and difficulties, the volume offers solutions and reflections to assist in overcoming the barriers which might be encountered whilst carrying out research of this nature.